Психологічний стан дітей шкільного віку з порушеннями фізичного та статевого розвитку, які виховуються у сім'ях - Погадаєва, Н. Л. (Clinical Endocrinology and Endocrine Surgery, 2011)
The article presents research findings that most children who are brought up in a family and having a growth retardation and delay puberty, marked by high levels of school anxiety, unlike their peers with normal development. Ñhildren 8-11 y.o. and 15-17 y.o. have significantly higher rates of different types of school anxiety during active formation in this period of interpersonal relations.